Cultivation of E. coli carrying a plasmid-based Measles vaccine constructs (4.2 kbp pcDNA3F) employing medium optimisation and pH-temperature induction techniques - Clarence M. Ongkudon; Raelene Pickering; Diane Webster; Michael K. Danquah (BioMed Central Ltd., 2011)
Background Plasmid-based measles vaccines offer great promises over the conventional fertilised egg method such as ease of manufacture and mimic wild-type intracellular antigen expression. The increasing number of clinical trials on plasmid-based measles vaccines has triggered the need to make more in less time.